Stock Exchange Disclosure and Market Development: An Analysis of 50 International Exchanges - FROST, CAROL ANN; GORDON, ELIZABETH A.; HAYES, ANDREW F. (Journal of Accounting Research, 2006)
This study examines associations between measures of stock exchange disclosure and market development at 50 of the member stock exchanges of the World Federation of Exchanges. We focus on stock exchange disclosure systems (rather than actual company disclosures) because this approach links stock exchange policy with desired outcomes related to market development (such as liquidity, trading activity, and market size relative to gross domestic product). We find strong support for the hypothesis that the strength of the disclosure system (disclosure rules, monitoring, and enforcement) is positively associated with market development, after controlling for legal system, legal protection of investors, market size, and several other potentially relevant explanatory variables.